2002
DOI: 10.1038/sj.bjc.6600103
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent effects of ZD1839 (‘Iressa’) in combination with cytotoxic treatment in human head and neck cancer

Abstract: Elevated levels of epidermal growth factor receptor in head and neck cancer have been extensively reported, and are correlated with poor prognosis. The combination of cisplatin and 5-fluorouracil is a standard treatment regimen for head and neck cancer, with radiation representing another therapeutic option. Six head and neck cancer cell lines were used to study the cytotoxic effects of combining ZD1839 ('Iressa'), a new selective epidermal growth factor receptor tyrosine kinase inhibitor, and radiation. Two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
60
1
5

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 41 publications
(42 reference statements)
3
60
1
5
Order By: Relevance
“…The cytotoxic effects resulting from this drug combination were analysed as described previously (Magné et al, 2002a). A mean combination index (according to Chou and Talalay, 1984) of 0.4 was found, which confirmed the existence of the previously reported synergistic cytotoxic activity (Magné et al, 2002a).…”
Section: Drug Administration Schedulesupporting
confidence: 80%
See 4 more Smart Citations
“…The cytotoxic effects resulting from this drug combination were analysed as described previously (Magné et al, 2002a). A mean combination index (according to Chou and Talalay, 1984) of 0.4 was found, which confirmed the existence of the previously reported synergistic cytotoxic activity (Magné et al, 2002a).…”
Section: Drug Administration Schedulesupporting
confidence: 80%
“…Similar enhancement of activity has also been observed in studies combining EGFR-targeting agents, particularly the monoclonal antibody IMC C225 (cetuximab), with ionizing radiation (Huang et al, 1999;Saleh et al, 1999;Bianco et al, 2000;Bonner et al, 2000;Milas et al, 2000). Other investigators (Williams et al, 2002) and this laboratory (Magné et al, 2002a) recently showed supra-additive effects between irradiation and ZD1839, confirming the radiosensitisation conferred by an EGFRtargeting agent. We also reported a synergistic interaction between ZD1839 and the cisplatin -5FU combination (Magné et al, 2002a).…”
mentioning
confidence: 53%
See 3 more Smart Citations